Documentation of ethnomedicinal plants used by the people living in reserved forests of semi-arid region Punjab Pakistan - Muhammad Waheed; Shiekh Marifatul Haq; Muhammad Azhar Jameel; Fahim Arshad; Rainer W. Bussmann (Ethnobotany Research and Applications, 2023)
Background: Ethnobotanical investigations serve as a foundation for comprehending the intricate interplay between plants and people within specific geographical regions, while also informing conservation strategies and priorities. The present study was conducted within the marginalized communities in the reserved forests of Punjab, Pakistan’s semi-arid region. Methods: The study participants were selected using random sampling techniques, and they underwent semi-structured interviews involving open-ended questions to gather the required data. Results: In total, 82 plant taxa were documented, representing 74 genera and 32 families. The predominant category was wild herbs (45 species), with whole plants (35 species) being commonly employed in drug preparations. These studied plants were noted for their efficacy in addressing 30 distinct ailments, with fever (33 species) and gastrointestinal disorders (28 species) being the primary conditions they were prominently used for. Conclusions: These findings validate the substantial plant-based knowledge held by the populations residing in the semi-arid region. Nonetheless, the rapid pace of urbanization, coupled with economic growth and evolving sociocultural dynamics, has posed challenges to the preservation of traditional wisdom. A notable decline has been observed in the count of herbal practitioners, with their successors displaying diminished interest in the field due to demanding work and limited profitability. As a result, the revitalization of existing traditional practices could potentially be achieved through initiatives such as organic product development, cultivating ethnospecies in home gardens, and establishing collaborations with herbal industries. Keywords: Ethnomedicine, Reserved Forest, local communities, semi-arid region, flora.